Cooperative guidance laws against highly maneuvering target with impact time and angle. (April 2022) - Wang, Zhikai; Fang, Yangwang; Fu, Wenxing; Wu, Zihao; Wang, Mingang
To address the issue that multiple missiles intercepting a highly maneuvering target simultaneously with desired angles, a novel cooperative guidance law based on the decoupled model in the line-of-sight (LOS) and normal LOS direction is proposed in LOS frame. However, there is control coupling in the two directions of the cooperative guidance model. In this article, we first decouple the guidance model and then separately design estimation decouple cooperative guidance law in two directions based on the decoupled model. The guidance law component in the LOS direction is designed with the integral sliding mode control and multi-agent consensus theory, where the combining disturbance is compensated by an adaptively estimated term. The guidance law component in the normal LOS direction is designed based on nonsingular terminal sliding mode control with fast power reaching law, and a nonlinear disturbance observer is introduced to estimate the combining disturbance. Then, the finite time convergence of time-to-go and LOS angle is proved. Finally, numerical simulation results demonstrate the effectiveness and superiority of the proposed cooperative guidance law.